Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.memsci.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ionic organic draw solutes in osmotic membrane bioreactors for water reuse

Abstract: The performance of two ionic organic draw solutes, namely sodium acetate (NaOAc) and ethylene-diaminetetra acetic acid disodium salt (EDTA-2Na), during osmotic membrane bioreactor (OMBR) operation was investigated in this study. Their performance was compared to that of sodium chloride (NaCl). A reverse osmosis (RO) process was integrated with OMBR to form an OMBR-RO hybrid system for draw solute recovery and clean water production. Results show that the NaOAc and EDTA-2Na draw solutes significantly reduced sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 54 publications
10
30
0
Order By: Relevance
“…This decrease in SOUR could be well correlated to the increase in salinity during the first week of operation. These observations are consistent with previous studies especially within the first two weeks of operation and could be attributed to the inhibition of elevated bioreactor salinity on biomass growth and activity (Luo et al, 2016a;Reid et al, 2006). Indeed, as can be seen in Fig.…”
Section: Biomass Activitysupporting
confidence: 93%
“…This decrease in SOUR could be well correlated to the increase in salinity during the first week of operation. These observations are consistent with previous studies especially within the first two weeks of operation and could be attributed to the inhibition of elevated bioreactor salinity on biomass growth and activity (Luo et al, 2016a;Reid et al, 2006). Indeed, as can be seen in Fig.…”
Section: Biomass Activitysupporting
confidence: 93%
“…Recently, several authors have investigated these critical issues in OMBR technology to improve its application. Luo et al [19] studied the salt reverse flux for water reuse in a OMBR using different draw solutions. They concluded that ionic organic draw solutes can mitigate salinity build-up in the mixed liquor.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of refractory OMPs and their biodegradation by-products adversely affects biodegradation potential of bacteria present in activated sludge [34]. In addition, OMPs concentrations are uncertain in sewage and conventional wastewater treatment facilities are unable to efficiently remove OMPs to the extent for reuse applications [2]. For example, commonly detected OMPs such as ibuprofen showed biodegradable removal of 75% whereas Estrone (E1) and 17-α-Ethinyl estradiol (EE2) achieved 83% and 44% removal [41].…”
Section: Membrane Bioreactors In Organic Micropollutants Removalmentioning
confidence: 99%
“…Rapid population growth, combined with increased agricultural and industrial undertakings is resulting in increased water demand and sewage production [1]. Thus, these persistent drivers of water stress are prompting interest in advanced wastewater treatment techniques that utilize alternative water sources, such as domestic wastewater for water reclamation [2,3]. However, with growing interest in reclaimed water use, safety warrants for health risks-especially when the diverse nature of organic micropollutants found in reclaimed water-must be taken into account [4].…”
Section: Introductionmentioning
confidence: 99%